These Gods Got Swagger: Avatars, Gameplay, and the Digital Performance of Hip Hop Culture in Machinima - Clay, Elonda (Bulletin for the study of religion, 2011)
This paper expands the topography of contexts in which research on hip hop and religion takes place by investigating the ways in which video game engines and video editing software are used by game players to produce films within virtual environments. My investigation highlights the online dramatic form of "machinima" (machine-cinema) - a creative, often unintended user adaptation of video game engines and movie-making software. I argue that ‘swagger’, a collective of black cultural expressions that signify confidence, success, rhythmic body movements, and highly stylized appearance, is reconfigured by gamers for virtual environments, resulting in the creation of highly stylized virtual worlds, the modding (modifying) of simulated characters, and the re-composing of the game’s narrative architecture into player-created storylines. In this regard, this article proposes that digital performances and emergent authorship have multiple implications for the study of African American religions.